RUNTUHNYA DOMINASI KELUARGA RATU ATUT DALAM PILKADA BANTEN 2024: ANALISIS DINAMIKA POLITIK LOKAL - Dwi Nurfaisal, Muhammad; Sari, Inrinofita (Ensiklopedia Sosial Review, 2025)
This study aims to analyze the factors that led to the collapse of Ratu Atut's family dominance in the 2024 Banten regional election. Using qualitative research methods and qualitative data analysis (QDA) through a descriptive approach, this study explores the local political dynamics that influenced the election outcome. Data was collected from online media sources, official websites, and relevant previous studies. Data processing was conducted using Nvivo 12 Plus software, with Crosstab Query features to visualize relationships between variables and Word Cloud to identify dominant words in the data. The results showed that four main factors caused the collapse of Ratu Atut's family dominance, namely changes in voter preferences that are more critical of integrity and transparency, the strengthening of organized opposition political movements, the increasing participation of the younger generation who utilize digital platforms, and the negative image of the family due to various legal cases. This research makes an important contribution in understanding the dynamics of political transition in Banten, which not only reflects the increasing political awareness of the people but also an opportunity to strengthen local democratic institutions.Keywords: Banten Election, Community Participation, Ratu Atut Family